2014
DOI: 10.1371/journal.pone.0114477
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Diversity of Feral Genetically Modified Oilseed Rape (Brassica napus L.) Despite a Cultivation and Import Ban in Switzerland

Abstract: Despite cultivation and seed import bans of genetically modified (GM) oilseed rape (Brassica napus L.), feral GM plants were found growing along railway lines and in port areas at four sites in Switzerland in 2011 and 2012. All GM plants were identified as glyphosate-resistant GM event GT73 (Roundup Ready, Monsanto). The most affected sites were the Rhine port of Basel and the St. Johann freight railway station in Basel. To assess the distribution and intra- and interspecific outcrossing of GM oilseed rape in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 33 publications
0
40
0
1
Order By: Relevance
“…Survival of oilseed rape outside cultivation areas is possible. Demographic studies and surveys have shown the ability of oilseed rape (B. napus) to establish self-perpetuating populations outside agricultural areas, mainly in seminatural and ruderal habitats in different countries (reviewed by Devos et al, 2012;Bauer-Panskus et al, 2013;COGEM, 2013;Hecht et al, 2014;Schulze et al, 2014;Katsuta et al, 2015;Busi and Powles, 2016;Nishizawa et al, 2016). oilseed rape is generally regarded as an opportunistic species, which can take advantage of disturbed sites (e.g.…”
Section: Potential Unintended Effects On Plant Fitness Due To the Genmentioning
confidence: 99%
“…Survival of oilseed rape outside cultivation areas is possible. Demographic studies and surveys have shown the ability of oilseed rape (B. napus) to establish self-perpetuating populations outside agricultural areas, mainly in seminatural and ruderal habitats in different countries (reviewed by Devos et al, 2012;Bauer-Panskus et al, 2013;COGEM, 2013;Hecht et al, 2014;Schulze et al, 2014;Katsuta et al, 2015;Busi and Powles, 2016;Nishizawa et al, 2016). oilseed rape is generally regarded as an opportunistic species, which can take advantage of disturbed sites (e.g.…”
Section: Potential Unintended Effects On Plant Fitness Due To the Genmentioning
confidence: 99%
“…Here, mixtures of OSR varieties as well as imported OSR seeds are handled. Schulze et al (2014) confirmed GM OSR spillage at such sites in Switzerland. Although import of GM OSR seeds is banned, GM OSR was found in the St. Johann railway station and the Rhine port of Basel.…”
Section: Identification Of Most Sensitive Linksmentioning
confidence: 52%
“…These four sites were ports and railway stations on the borders to France and Italy. The feral plants probably originated from spillage of contaminated OSR seed from freight trains (Hecht et al, 2014;Schulze et al, 2014Schulze et al, , 2015. Spillage of GM OSR seeds along transportation routes was also confirmed in Japan where cultivation of GM OSR is also prohibited (Saji et al, 2005;Kawata et al, 2009;Nishizawa et al, 2009Nishizawa et al, , 2010Aono et al, 2011;Mizuguti et al, 2011), the United States (in North Dakota 80% of feral OSR proved to be GM: Schafer et al, 2011;Sagers et al, 2012) and Canada (Yoshimura et al, 2006;Knispel et al, 2008;Beckie and Warwick, 2010;Knispel and McLachlan, 2010).…”
Section: Oilseed Rape As a Model System For Seed Spillage Along Transmentioning
confidence: 92%
“…Seed spill can also occur outside the fields and along transport routes, potentially leading to HR feral plants that may persist over large spatial and temporal scales [101]. HR feral oilseed rape plants have been found along transport routes in the US [102], in Switzerland [103] and Japan [104], in regions where they had never been grown.…”
Section: Reviewmentioning
confidence: 99%